A Clip-with-Line Traction Suture Method for Closing Mucosal Defects after Endoscopic Submucosal Dissection. (3rd March 2021) - Wang, Chong; Wang, Yiting; Li, Yuanyuan; Zeng, Sheng; Chen, Youxiang; Li, Guohua
Abstract : Endoscopic submucosal dissection (ESD) is a technically difficult endoscopic procedure for treating gastrointestinal diseases. Procedure time is longer, and complications such as mucosal defects, intraoperative perforation, and bleeding occur frequently. Here, to solve these problems, we described the clip-with-line traction suture method that applied and performed for closing mucosal defects after ESD in three representative cases.